Strengthening Creative Economic Resources Through Designing Appropriate Regulatory Model in Managing and Optimising Cultural Property - Hayyan Ul Haq (International Conference On Law, Business and Governance (ICon-LBG), 2013)
This work is aimed at exploring, finding and formulating some appropriate regulatory models inoptimising cultural property products. This idea has been inspired by à huge national potentials in culturalproperty which has economic values. The concrete economic values of cultural property can bemanifested through intervetion of Intellectual property and folklore and cultural property regime.Therefore, this works shows the important role of government in designing appropriate policies andregulations in managing and optimizing cultural property products. It introduces two approaches: (i)normative and (ii) institutional approaches in visualising and manifesting the above objectives. At thenormatieve level, this work identify, explore, and formulate some potential regulations which stem fromthe core regulations related to cultural property products, such as: intellectual property, particularly patentand copyright; as well as folklore and traditional culture regime. It explorer and formulates potential andstrategic policies, either at the national or regional level to optimise some opportunities in the intellectualproperty, folklore and traditional cultural regime. In this respect, how to interprete and embody therecognition of cultural property, such as traditional knowledge and traditional culture into appropriateregulatory models. While, at the institutional level, this work introduces the inclusive museums that mayfunction as conservator, educational, and creative economische medium in maintaining and improving thequality, function and sustainability of cultural property protection and development